Coping with aging - Lazarus, Richard S. (Oxford University Press, 2006)
"Coping with Aging" is the final project of the late Richard S. Lazarus, the man whose landmark book "Emotion and Adaptation" put the study of emotion in play in the field of psychology. In this volume, Lazarus examines the experience of aging from the standpoint of the individual, rather than as merely a collection of statistics and charts. This technique is in line with his long-standing belief that experiences should be looked at in their specific contexts, rather than squeezed into an overly general statistical viewpoint that loses the subjects' motivations. Drawing on his five decades of pioneering research, Lazarus looks aging, emotion, and coping, and stability and change in both environment and personality. Because Lazarus mixes academic rigor with everyday examples, this volume will be both useful to scholars and accessible to the lay audience that has so much gain from a systematic understanding of aging and emotion